대구광역시 도시근교농업 종합발전대책 연구 - 박문호 (한국농촌경제연구원, 2008)
The world is currently experiencing further market liberalization alongside current trade negotiations and agreements such as DDA and FTAs. The changes of agricultural policies in the context of market opening focus on multilateral functions of agriculture. The changes in agricultural policies were made to compete with imports and they are predicted to have a strong influence on local agricultural sectors. In particular, agricultural investment and related projects of local self-governments constitute a major factor in determining the quality of life of local farmers and the competitiveness of production and income level of each farm household. Accordingly, the formulation and implementation of agricultural plans by local self-governments hold a significant place in the nation's overall agricultural policy. This study examines regional, environmental and socio-economic features of the agricultural sector and rural communities of Daegu in the context of internal and external environments surrounding its agriculture and rural communities. The primary goal of this study is to make master plan suggestions for Daegu's suburban agriculture and communities by assessing their strengths and weaknesses. The concrete purposes of this study are as follows: The first is to establish a direction for the development of agriculture and rural regions of Daegu based on the investment plan of Article 119 of the government's "Agriculture and Rural Development Countermeasures." The second purpose is to present a vision and a development strategy for agriculture and rural regions of Daegu after researching their available resources as of today. The third is to present a method of selecting and intensively raising specialized crops. And the last is to devise measures of guaranteeing agriculture's competitiveness through environment-friendly agricultural products. The vision and development strategy for agriculture and rural region of Daegu. The development vision for agriculture and rural region of Daegu lies on “the green industrialization for both farmers and consumers.” In this respect, this study sets a goal of improving farmers' quality of life through proper development and conservation of nature. To achieve this objective, this study presented four innovation strategies on agricultural industries, circulation of agricultural products, rural development, and development of agricultural human resources and support system. The comprehensive innovation strategies could be summarized as follows: 1) The innovation strategy on agricultural industries According to the city development plan of Daegu, the areas where a large agricultural production base can be maintained on a collective level are projected to be limited to water supply protection zones and development restricted areas. Under this projection, the agricultural production base of Daegu can be classified into the Mt. Palgong and Kumho River region and the Nakdong River and Mt. Bisul region. Based on these regions, development plans for major specialty products of Daegu can be formulated. 2) The innovation strategy on the circulation of agricultural products As a major city in the southeastern part of Korea, Daegu has a large consuming base and it is expected to grow with the ongoing construction of new towns called "innovation cities." Furthermore, the preference for high quality and safe agricultural products has been expanding, and city dwellers' contact with rural regions will grow together with their need for leisure or recreational tours. Such being the case, the trends are becoming opportunities for the marketing of Daegu agricultural products. 3) The innovation strategy on rural region development The basic principles of rural development strategy could be summarized as follows: First, agricultural and ecological tourism projects, such as green experience tours, should be developed to correspond to the liking of Daegu citizens. Second, the real income of farmers should be increased by enabling them to expand their farming businesses in link with agricultural processing and marketing as well as eco-tourism. At the same time, the rural development strategy should strengthen the rural residents' capability and contribute to the balanced development of the region. Third, by building an eco-friendly image of Daegu, the city can raise the overall brand value of its agricultural products and inspire the local government to invest in rural-urban exchange projects. 4) The innovation strategy on agricultural human resources and support system The new paradigm of knowledge-based agriculture requires farmers who can create knowledge and utilize it to increase the value-added of agricultural products. Therefore, it is necessary to build a support system that can foster and improve human resources armed with new knowledge in the agricultural sector. Investment plans are essential for carrying out the aforementioned strategies. First, in selecting an investment project, it is necessary to comprehensively examine and consider the motivation of participating enterprises, ripple effects on the region, and the opinion of local residents. Second, the investment plan should be balanced with the central government's investment plan in consideration of the plan's high dependence on national expenditure grants and financial circumstances. Third, the investment plan should be selected by considering the overall framework of Daegu's other related investment plans. Researchers: Park Moon-Ho, Kuk Sung-Yong, Yoon Byeong-Seok, Lee Moon-Ho Research period: 2007. 11. - 2008. 11. E-mail address: mhpark@krei.re.kr